2015
DOI: 10.1007/s10916-015-0363-7
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Factors on Extended Hospital Length of Stay in Patients with AMI: Laboratory and Administrative Data

Abstract: The length of hospital stay (LOS) is an important measure of efficiency in the use of hospital resources. Acute Myocardial Infarction (AMI), as one of the diseases with higher mortality and LOS variability in the OECD countries, has been studied with predominant use of administrative data, particularly on mortality risk adjustment, failing investigation in the resource planning and specifically in LOS. This paper presents results of a predictive model for extended LOS (LOSE - above 75th percentile of LOS) usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 35 publications
0
29
1
Order By: Relevance
“…LOS for inpatients with more serious conditions was longer than other patients, and numerous studies have drawn similar conclusions. 29 These results differ from those presented in previous studies, which reported that more resources in high-volume hospitals might result in lower costs. Our study found that a lower volume was related to lower costs.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…LOS for inpatients with more serious conditions was longer than other patients, and numerous studies have drawn similar conclusions. 29 These results differ from those presented in previous studies, which reported that more resources in high-volume hospitals might result in lower costs. Our study found that a lower volume was related to lower costs.…”
Section: Discussioncontrasting
confidence: 76%
“…One possible explanation for the difference in LOS for patients between medium‐ and high‐volume groups is that patients with more serious conditions are more likely to be treated in higher volume hospitals with a higher profile. LOS for inpatients with more serious conditions was longer than other patients, and numerous studies have drawn similar conclusions . These results differ from those presented in previous studies, which reported that more resources in high‐volume hospitals might result in lower costs.…”
Section: Discussionmentioning
confidence: 96%
“…A Recall (58%) and Specificity (73%), with a cut-off of 0.26, and a discriminatory capacity (area under the ROC curve [AUC] of 0.702) were observed for the population of patients with a primary diagnosis of AMI, who were discharged alive and for the variables defined in the previous model (VM). According to the data presented in Table 3, there is a decrease in the predictive capacity of the VM compared to the results obtained in the model by Magalhães et al (13). The VM considered LOSE ≥ 7 days.…”
Section: Validation Modelmentioning
confidence: 76%
“…Seventy-four articles were retained for full-text reviews and additional 54 articles were excluded as they were (a) not A summary of the information about study characteristics and key findings is presented in Table 1. Most of the studies were performed in the USA (Deedwania et al, 2017;Dunlay et al, 2012;Oanh Kieu et al, 2018;Tisminetzky et al, 2014;Tisminetzky et al, 2015) and Australia (Wu, Chang, Courtney, & Kostner,2012b;Wu, Chang, & McDowell, 2009;Wu & Chang, 2008;Wu, Chang, Courtney, & Ramis, 2012a;Wu et al, 2017) (five studies in each); three studies were performed in Taiwan (Carral et al, 2003;Chiang et al, 2013;Hung et al, 2013); and one study each, was conducted in Canada (Southern et al, 2014), Italy (Valent, Tonutti, & Grimaldi, 2017), Spain (Rodriguez-Padial et al, 2017), Portugal (Magalhães, Lopes, Gomes, & Seixo, 2016), India (Kamalesh, Subramanian, Ariana, Sawada, & Tierney, 2005), the UK (Loudon et al, 2016), and France (Colin, Lafuma, & Gueron, 2007). The majority of articles used a FIGURE 1 PRISMA flow diagram of the study selection process…”
Section: Resultsmentioning
confidence: 99%
“…The remaining four articles examined the predictors of a longer LOS. Magalhães et al (2016) developed a model to predict extended LOS, which was defined as above the 75th percentile of LOS, and the results indicated that diabetes with complications were robust predictors, that showed the highest odds of extended LOS. In addition, Loudon et al (2016) and Valent et al (2017) found that diabetes is an independent predictor of increased LOS.…”
Section: Author Manuscriptmentioning
confidence: 99%